The knowledge of Accounting students regarding the Code of Ethics - Cunha, Karina Silveira da (2020)
The Accountant’s Professional Code of Ethics (CEPC) aims to set the way which accountants must follow in the exercise of their profession and with regards to their professional class, and knowledge of its contents is one of the components of the Sufficiency Exam of the Federal Accounting Council. This research aims to verify the level of knowledge that the students of the Accounting Sciences Course in the Federal University of Santa Catarina have with regards to the CEPC. The qualitative research was done via a survey based on questions from the Sufficiency Exam of the Federal Accounting Council. The research had the participation of 101 students enrolled in the 2nd and 4th stages of the Course. The results show that the average number of correct answers for students who took the class (Ethics and Political Philosophy) is statistically higher than that of students who did not take the class. The median of that count for the students who took the class is twice that of the students who did not take the class. These results support the conclusion that taking the class positively impacts the students’ performance on ethics-related questions. However, the analysis, per question, of the performance of both groups revealed that the proportion of correct answers for the students who already took the class is statistically higher than that of the students who did not take the class yet in only 5 of the 18 questions analyzed. These results, considering the content of the questions in which there was an increase in performance, support the conclusion that taking the class positively impacts the students’ performance in a restricted and small number of questions.